Ontologi Relasi Zakat Profesi dan Relevansinya terhadap Implementasi Pola Konsumtif Kreatif dalam SekuritasPasar Modal - Ainur Rahman Hidayat; Fatati Nuryana (Media Syari'ah, 2017)
This article examines the relation ontolog y zakat profession and its relevancet o the implementation of creative consumptive pattern in which there is a shift in the meaning of zakat interpretation of fiqh issues as doctrinal truth becomes a social problem-empirical. This article makes charity the profession as part of the search for solutions to various social problems Muslims present and future.